Palynological analysis from a bush karoo rat (Otomys unisulcatus) lodge near Prince Albert, South Africa - Patrickson, Shela (Department of Biological Sciences, 2017)
The "desertification" debate surrounding the Karoo Biome of South Africa has recently inspired much research in this region. The preservation of pollen in middens in arid environments from different parts of the world has great potential for the reconstruction of past vegetation. A lodge of the bush karoo rat (Otomys unisulcatus) was excavated near Prince Albert, South Africa, and the high numbers of well-preserved pollen grains was analysed. The vegetation reconstruction suggested that there was a decline in grasses over the whole sequence, while the vegetation experienced several short-term fluctuations throughout the time period. The ages within the lodge were uncertain, although the material is likely to be modern. The palynological analysis appear to be reliable and corresponds relatively well with other studies. The lodges of these species could therefore provide an exciting new source of historical pollen in the arid regions of southern Africa.